A preparation process of perfluoroalkyl series functional chemicals
Patent Information
- Application Number
- CN202611058890.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-13
AI Technical Summary
1)环保压力巨大:反应结束后需大量水洗除酸,产生大量含氟含酸废水,处理成本极高
1.本发明的起始原料全氟烷基链长严格控制在C6及以下,产品PFOA/PFOS含量<1ppb,完全符合中国《重点管控新污染物清单》(2024年)、欧盟REACH法规及美国EPA的PFAS管控要求;且本发明第四步采用固体酸替代均相酸,结合pH响应自分离技术,从源头消除含氟酸性废水排放90%以上,每吨产品减少废水排放0.8吨以上。
Smart Images

Figure REF-OBJ-1784188483365-000001 
Figure REF-OBJ-1784188483365-000002 
Figure REF-OBJ-1784188483365-000003
Abstract
Description
Technical Field
[0001] This invention relates to the field of fluorine-containing fine chemical technology, and in particular to a preparation process for a series of functional chemicals containing perfluoroalkyl groups. Background Technology
[0002] Perfluoroalkyl compounds, due to their extremely low surface energy, are widely used in textile finishing, high-end coatings, electronic cleaning, and functional polymers. Traditional processes often employ electrolytic fluorination or tetrafluoroethylene telomerization to prepare perfluorooctyl (C8) derivatives. However, with increasingly stringent domestic and international regulations on perfluorinated and polyfluoroalkyl substances (PFAS), perfluorooctanoic acid (PFOA) and perfluorooctane sulfonyl compounds (PFOS) have been included in the "List of Key Controlled New Pollutants," severely restricting the production and use of C8 products.
[0003] Currently, the industry is shifting towards short-chain perfluoroalkyl compounds with carbon chains shorter than C8 as alternatives. However, this approach generally faces technological bias: the shorter the perfluoroalkyl chain, the worse its surface energy reduction effect, resulting in a significant decrease in water and oil repellency. How to achieve the application performance of traditional long-chain products while remaining environmentally friendly through molecular design and process innovation is a pressing technical challenge in this field.
[0004] Furthermore, traditional preparation processes often employ homogeneous strong acid catalysts (such as p-toluenesulfonic acid and concentrated sulfuric acid) in the esterification or transesterification steps. This process route has the following significant drawbacks: 1) Huge environmental pressure: After the reaction is completed, a large amount of water is needed to wash away the acid, which generates a large amount of fluoride-containing and acid-containing wastewater, and the treatment cost is extremely high.
[0005] 2) High energy consumption for separation: Homogeneous catalysts are difficult to recover, and acid residues must be thoroughly removed before distillation, otherwise product polymerization or equipment corrosion may occur at high temperatures.
[0006] 3) Difficulty in separating solid catalysts: Although conventional solid acid catalysts can solve the problem of continuous production, nano- or micron-sized solid catalysts need to be separated by high-speed centrifugation or precision filtration, which results in high equipment investment and operating energy consumption, and the filter cartridges are easily clogged.
[0007] Therefore, there is an urgent need to develop a green preparation process that can both ensure the application performance of short-chain products and achieve low energy consumption and high-efficiency recovery of catalysts. Summary of the Invention
[0008] To address the shortcomings of existing technologies, this invention provides a preparation process for a series of functional chemicals containing perfluoroalkyl groups. This environmentally friendly process not only enables short-chain products to achieve the application performance of traditional long-chain products, but also achieves low-energy in-situ self-separation of solid acid catalysts by introducing a pH-responsive aggregation and precipitation mechanism, thereby eliminating the discharge of fluoride-containing acidic wastewater at the source.
[0009] To achieve the above objectives, the present invention adopts the following technical solution: A process for preparing a series of functional chemicals containing perfluoroalkyl groups includes the following four steps: Step 1: Addition reaction Reaction equation: RfX + CH2 = CH2 → RfCH2CH2X; Wherein, Rf is a perfluoroalkyl group having 1-6 carbon atoms, and X is I or Br.
[0010] The perfluoroalkyl group includes, but is not limited to, perfluoromethyl, perfluoroethyl, perfluoron-propyl, perfluoroisopropyl, perfluoron-butyl, perfluoroisobutyl, perfluoron-hexyl, and perfluoroisohexyl. The X group is iodine or bromine. Starting materials include, but are not limited to, trifluoroiodine (bromine)methane, pentafluoroiodine (bromine)ethane, perfluoron-propyl iodine (bromine), perfluorobutyl iodine (bromine), perfluoroisobutyl iodine (bromine), perfluoroneopentyl iodine (bromine), and perfluorohexyl iodine (bromine).
[0011] Reaction conditions: Temperature 30-200℃, preferably 50-150℃, more preferably 60-90℃; Pressure 0-1.5MPa, preferably 0.35-0.70MPa.
[0012] Catalyst: Free radical initiator, preferably azobisisobutyronitrile (AIBN). Peroxides and their derivatives, palladium on carbon, etc., can also be used. The amount of catalyst used is 0.1% to 2.0% of the mass of perfluoroalkyl iodine.
[0013] Reaction Mechanism: AIBN undergoes homolytic cleavage under heating conditions (>60℃) to generate isobutyronitrile radicals, releasing nitrogen gas. The isobutyronitrile radicals attack the CI bond of the perfluoroalkyl iodide (bond energy approximately 218 kJ / mol, relatively weak), resulting in iodine atom transfer and the formation of perfluoroalkyl radicals. These perfluoroalkyl radicals then undergo a radical addition reaction with ethylene to generate perfluoroalkylethyl radicals, which abstract iodine atoms from the starting material or solvent, completing the chain propagation and forming perfluoroalkylethyl iodide. This reaction is a radical chain reaction, initiated and sustained by AIBN.
[0014] Specific operating steps: After adding the metered catalyst to the reactor, evacuate and purge twice with nitrogen, then evacuate again. Add perfluoroalkyl iodine to the reactor, start stirring and heat to 40°C, then add ethylene gas to 0.50–0.70 MPa, maintaining the temperature at 60–90°C. When the reactor pressure drops to 0.0–0.35 MPa, add ethylene. Repeat the above operating steps until the reactor pressure no longer drops significantly, then maintain the temperature and pressure for 2 hours to complete the reaction. Take samples for testing until the samples are qualified (raw material conversion rate ≥98%).
[0015] Step 2: Elimination of the reaction Reaction equation: RfCH2CH2X + AOH → RfCH=CH2 + AX + H2O; Wherein, Rf is a perfluoroalkyl group having 1-6 carbon atoms, X is I or Br, and A is Na, K or Li.
[0016] Reaction conditions: Temperature 25-80℃, preferably 50-70℃; Pressure 0-1.0MPa.
[0017] Reaction reagents: Alkali metal hydroxide alcoholic solution, preferably potassium hydroxide ethanol solution or potassium hydroxide methanol solution. The alkali concentration is 5% to 30% (mass fraction), and the molar ratio of alkali to raw material is 1.0 to 1.5:1.
[0018] Reaction Mechanism: Under the action of a strong base, the β-hydrogen (the hydrogen on the carbon adjacent to iodine) of the perfluoroalkyl ethyl iodine is abstracted by the base. Due to the strong electron-withdrawing inductive effect of the perfluoroalkyl group, the acidity of the β-hydrogen is enhanced (pKa approximately 20-22), making it easier for the base to abstract it. Simultaneously, the CI bond breaks, the iodide ion leaves, and a bimolecular elimination reaction (E2 mechanism) occurs. The reaction proceeds through a five-membered cyclic transition state, with the β-hydrogen, α-carbon, β-carbon, and leaving group I coplanar, to generate perfluoroalkyl ethylene in one step. This reaction is stereospecific.
[0019] Specific operating steps: After adding a measured amount of methanol and perfluoroalkyl ethyl iodine to the reaction vessel, start stirring and heat to 50-60℃. Add a 15% concentration of potassium hydroxide in methanol using a metering pump, maintaining the temperature at 60-70℃. After the addition is complete, maintain the temperature for 2 hours, then add a measured amount of water. Let stand for 30 minutes, separating the lower layer of organic matter (perfluoroalkyl ethylene density > 1.5 g / mL). After sampling and analysis confirms the material is qualified, terminate the reaction. The crude product is then distilled to obtain perfluoroalkyl ethylene with a purity ≥ 99%.
[0020] Step 3: Addition reaction Reaction equation: RfCH=CH2 + HR1OH → RfCH2CH2R1OH; Wherein, Rf is a perfluoroalkyl group having 1-6 carbon atoms, and R1 is an alkyl or aromatic group.
[0021] The range of perfluoroalkyl groups is the same as in the first step. The alcohols used in this reaction include, but are not limited to, methanol, ethanol, propanol, isopropanol, tert-butanol, neopentyl alcohol, o-(p-)methylphenol, o-(p-)chlorophenol, etc.
[0022] Reaction conditions: temperature 120-180℃, preferably 150-165℃; pressure 1.2-2.5MPa.
[0023] Catalyst: Lewis acid catalyst, preferably boron trifluoride diethyl ether complex (BF3·Et2O). Supported BF3, peroxide, etc., can also be used. The catalyst dosage is 0.5% to 5.0% of the mass of perfluoroalkylethylene.
[0024] Reaction Mechanism: Boron trifluoride, as a Lewis acid, has an empty p orbital in its boron atom, which coordinates with the lone pair of electrons of the oxygen atom in the alcohol hydroxyl group to form an O→B coordinate bond. This coordination enhances the polarity of the OH bond in the alcohol hydroxyl group, making the hydrogen more acidic, and simultaneously enhancing the nucleophilicity of oxygen. Simultaneously, BF3 polarizes the double bond of perfluoroalkyl vinyl, shifting the electron cloud of the double bond to one end, forming a partially positive charge center. The activated alcohol molecule undergoes electrophilic addition to the activated double bond, via a cyclic transition state, to form perfluoroalkyl propanol. The strong electron-withdrawing effect of the perfluoroalkyl group makes the double bond electron-deficient, favoring electrophilic addition.
[0025] Specific operating steps: After adding a measured amount of alcohol and a portion of the catalyst (20% of the total amount) to the reactor, start stirring and heat to 150-165℃. Slowly add a perfluoroalkyl vinyl solution containing the remaining catalyst using a metering pump, controlling the addition time over 2-4 hours and the temperature at 155-165℃. After the addition is complete, maintain the temperature for 1 hour, take a sample for analysis, and after passing the analysis, cool down and discharge the product. The crude product is then distilled to obtain perfluoroalkyl propanol with a purity ≥99%.
[0026] Step 4: Transesterification and Intelligent Separation Reaction equation: RfCH2CH2R1OH+CH2=CH-COOR2→RfCH2CH2R1OCOCH=CH2+R2OH; Wherein, Rf is a perfluoroalkyl group having 1-6 carbon atoms, and R2 is an alkyl group (methyl or hydrogen).
[0027] The range of reactants that can be selected includes, but is not limited to, methyl acrylate and methyl methacrylate.
[0028] Reaction conditions: Temperature 70~150℃, preferably 100~125℃; Pressure -0.1~0.5MPa (negative pressure can be used in the later stage).
[0029] Catalyst: Solid acid catalyst with surface modified with pH-responsive polymer.
[0030] The solid acid catalyst support is selected from Nafion perfluorosulfonic acid resin and sulfuric acid-promoted zirconium oxide (SO4). 2- Any one of (ZrO2) or sulfonated polystyrene-divinylbenzene resin, preferably Nafion NR50 perfluorosulfonic acid resin.
[0031] The pH-responsive polymer is any one of poly(2-dimethylamino)ethyl methacrylate (PDMAEMA), poly(4-vinylpyridine) (P4VP), or polymethacrylic acid (PMAA), with PDMAEMA being preferred.
[0032] Catalyst preparation method (Nafion@PDMAEMA): (1) Carrier activation: Nafion NR50 resin was refluxed with anhydrous ethanol for 12 hours and dried under vacuum at 60°C. It was then placed in a plasma cleaner and treated for 5 minutes in an oxygen atmosphere at 100W to generate oxygen-containing active groups such as hydroxyl and carboxyl groups on the surface.
[0033] (2) Initiator anchoring: The activated resin was immersed in anhydrous dichloromethane solution containing 2-bromoisobutyryl bromide (BiBB, 10 mM), and a catalytic amount of triethylamine was added. The reaction was carried out at room temperature for 12 hours. The resin was washed successively with dichloromethane and ethanol, and dried under vacuum to obtain Nafion-Br.
[0034] (3) SI-ATRP grafting: DMAEMA monomer (5.0 g), Nafion-Br (2.0 g), PMDETA ligand (0.11 g), and anhydrous methanol (15 mL) were added to a Schlenk flask. The mixture was subjected to a three-cycle process of liquid nitrogen freezing, vacuuming, and thawing to remove oxygen. CuBr (0.046 g) was added under nitrogen protection, and the mixture was sealed and reacted at 40°C for 6-12 hours. The reaction was terminated by exposure to air, filtered, and washed successively with methanol, deionized water, EDTA aqueous solution, and methanol. The mixture was then dried under vacuum at 40°C to obtain the Nafion@PDMAEMA catalyst.
[0035] Composite polymerization inhibitor system: A composite polymerization inhibitor system consisting of a phenolic polymerization inhibitor and a free radical scavenger is added throughout the reaction process. The phenolic polymerization inhibitor is p-hydroxyanisole (MEHQ), and the free radical scavenger is phenothiazine. The mass ratio of MEHQ to phenothiazine is 2:1 to 5:1, and the total amount of composite polymerization inhibitor is 200 to 500 ppm of the total mass of the reaction solution.
[0036] Transesterification mechanism: The sulfonic acid groups (-SO3H) on the surface of the solid acid catalyst provide protons (H+). + The proton first binds to the carbonyl oxygen of methyl methacrylate, increasing the positive charge and electrophilicity of the carbonyl carbon. The hydroxyl oxygen of perfluoroalkyl propanol then nucleophilically attacks the activated carbonyl carbon, forming a tetrahedral intermediate. After proton transfer, the intermediate loses one molecule of methanol to generate the target ester product. The catalyst then releases a proton, completing the catalytic cycle.
[0037] pH-responsive aggregation and precipitation mechanism: PDMAEMA is a cationic smart polymer with a pKa of approximately 7.0-7.5 for its tertiary amine side chain groups.
[0038] Reaction Stage (Acidic Environment): The transesterification reaction proceeds under solid acid catalysis, and the system is weakly acidic (pH ≈ 4-6). At this pH, the tertiary amine groups on the PDMAEMA chain undergo protonation (-N(CH3)2 + H+). + →-N + H(CH3)2) carries a positive charge. Electrostatic repulsion occurs between the positively charged polymer chains, which simultaneously extend fully in a good solvent (reaction solution). The catalyst particles are uniformly dispersed in the reaction solution due to electrostatic repulsion and steric hindrance, fully exposing the acidic active sites and ensuring high catalytic efficiency.
[0039] Separation stage (alkaline environment): After the reaction is complete, add an alkali (such as triethylamine or ammonia) to the system to adjust the pH to 7.5–9.0. At this pH, the tertiary amine groups on the PDMAEMA chain undergo deprotonation (-N... + H(CH3)2+OH - →-N(CH3)2+H2O), losing its positive charge. The hydrophobicity of the polymer chains increases, and the solubility in water / alcohol decreases, causing the molecular chains to shrink and curl. The surface of the catalyst particles changes from hydrophilic to hydrophobic, and the particles attract each other and aggregate due to hydrophobic interactions, forming larger aggregates (particle size increases from nanometer / micrometer to millimeter), which spontaneously and rapidly settle to the bottom of the reactor under gravity.
[0040] Specific operating steps: Add a measured amount of perfluoroalkyl propanol, methyl acrylate / methyl methacrylate (molar ratio 1:1.2–1:1.5), Nafion@PDMAEMA catalyst (1%–5% of propanol mass), MEHQ, and phenothiazine to the reactor. Start stirring and heat to 80–125°C. Gradually remove the generated methanol azeotrope through a distillation column condenser, maintaining the temperature at 100–125°C. During the later stages of the reaction, as the reactor temperature rises, use negative pressure to regulate and control the reaction temperature. When no azeotrope is generated, take a sample for analysis. Stop the reaction when the propanol content in the raw material is ≤1.5%.
[0041] After the reaction was complete, the material was cooled to 60°C. Triethylamine was slowly added dropwise while stirring until the pH of the system stabilized at 8.5. Stirring was continued for 30 minutes, during which the catalyst particles were observed to rapidly agglomerate and completely settle to the bottom of the vessel within 2 minutes after stirring was stopped. The supernatant was transferred to a distillation vessel to remove excess unreacted acrylate and light component impurities, followed by vacuum distillation to obtain the target product with a purity ≥99%.
[0042] Catalyst regeneration: Add 0.1 mol / L dilute sulfuric acid to the catalyst settled at the bottom of the reactor for washing, restore the pH to 3.0-4.0, and the catalyst is reprotonated to restore its dispersibility. After filtration and drying, it can be directly used in the next batch. No significant activity degradation was observed after more than 10 cycles of use.
[0043] Compared with the prior art, the beneficial effects of the present invention are: 1. The starting material of this invention has a perfluoroalkyl chain length strictly controlled to C6 and below, and the PFOA / PFOS content of the product is <1ppb, which fully complies with China's "List of Key Controlled New Pollutants" (2024), the EU REACH regulation and the US EPA's PFAS control requirements; and in the fourth step of this invention, solid acid is used to replace homogeneous acid, combined with pH-responsive self-separation technology, which eliminates more than 90% of the discharge of fluoride-containing acidic wastewater from the source, reducing wastewater discharge by more than 0.8 tons per ton of product.
[0044] 2. This invention utilizes the molecular structure design of branched alcohols such as isopropyl to achieve surface properties of short-chain perfluoroalkyl acrylates that meet or exceed those of traditional C8 products. Mechanism explanation: The branched structure generates a steric hindrance effect, inducing the perfluoroalkyl chains to align more closely on the surface in a direction more perpendicular to the substrate. This increases the enrichment density of CF3 end groups, reducing the surface energy from 18-20 mN / m for traditional C6 to 12-13 mN / m, and increasing the water contact angle from approximately 100° to over 115°.
[0045] 3. This invention utilizes the pH-responsiveness of PDMAEMA to achieve in-situ aggregation and sedimentation of the catalyst. Mechanism explanation: Under acidic reaction conditions (pH 4-6), PDMAEMA protonates and becomes positively charged, the polymer chains extend, the catalyst is uniformly dispersed, and catalytic activity is fully expressed; when adjusted to weakly alkaline conditions (pH 7.5-9.0), PDMAEMA deprotonates and hydrophobically shrinks, causing the catalyst particles to spontaneously aggregate and settle, completing solid-liquid separation within 2 minutes. The separation energy consumption is only 13% of centrifugation and 6% of precision filtration.
[0046] 4. The catalyst in the fourth step of this invention has a long cycle life. PDMAEMA is covalently grafted onto the Nafion surface via SI-ATRP, and does not dissolve or detach during swelling and expansion in alcohol solvents. pH-responsive aggregation is a physical process that does not damage the acidic active sites. The catalyst can be recycled 10 times with an activity decrease of <3%, significantly superior to mechanical filtration recovery of unmodified solid acids.
[0047] 5. The reaction conditions in each step of this invention have been systematically optimized, and the overall yield is stabilized at 80-83% (C3-C6 series). The synergistic effect of the composite polymerization inhibitor system (MEHQ + phenothiazine) results in polymerization losses of only 0.7% during the reaction and distillation stages, with product purity ≥99% and color ≤15 APHA.
[0048] 6. This invention eliminates the need for expensive separation equipment such as centrifuges and precision filtration systems, as well as water washing and neutralization processes and associated wastewater treatment facilities. Based on an annual production of 1000 tons of product, it saves approximately 600,000 yuan in equipment investment and approximately 350,000 yuan in annual operating costs. Detailed Implementation
[0049] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0050] The present invention will be described in detail below through 10 sets of examples and comparative examples. The experimental conditions, data results, and mechanism analysis of each example and comparative example are detailed below: Table 1. Overview of Experimental Design
[0051] Preparation Example 1. Preparation of Nafion@PDMAEMA catalyst: (1) Carrier activation: Nafion NR50 resin was refluxed with anhydrous ethanol for 12 hours and dried under vacuum at 60°C. It was then placed in a plasma cleaner and treated for 5 minutes in an oxygen atmosphere at 100W to generate oxygen-containing active groups such as hydroxyl and carboxyl groups on the surface.
[0052] (2) Initiator anchoring: The activated resin was immersed in anhydrous dichloromethane solution containing 2-bromoisobutyryl bromide (BiBB, 10 mM), and a catalytic amount of triethylamine was added. The reaction was carried out at room temperature for 12 hours. The resin was washed successively with dichloromethane and ethanol, and dried under vacuum to obtain Nafion-Br.
[0053] (3) SI-ATRP grafting: DMAEMA monomer (5.0 g), Nafion-Br (2.0 g), PMDETA ligand (0.11 g), and anhydrous methanol (15 mL) were added to a Schlenk flask. The mixture was subjected to a three-cycle process of liquid nitrogen freezing, vacuuming, and thawing to remove oxygen. CuBr (0.046 g) was added under nitrogen protection, and the mixture was sealed and reacted at 40°C for 6-12 hours. The reaction was terminated by exposure to air, filtered, and washed successively with methanol, deionized water, EDTA aqueous solution, and methanol. The mixture was then dried under vacuum at 40°C to obtain the Nafion@PDMAEMA catalyst.
[0054] Example 1. Standard preparation process of perfluorohexylpropyl methacrylate (C6 series): Step 1 – Addition Reaction: Add 1000g (2.24mol) of perfluorohexyl iodine (C6F) to a 2L autoclave. 13I) and 5g AIBN (0.5wt%) were added, and the mixture was purged with nitrogen three times. The temperature was raised to 80℃, and ethylene was introduced to maintain a pressure of 0.55±0.05MPa. Ethylene was added whenever the pressure decreased during the reaction until the pressure remained stable for 2 hours. The mixture was then cooled and discharged to obtain perfluorohexylethyl iodide (C6F). 13 CH2CH2I) 1045g, GC analysis showed a purity of 98.7% and a yield of 96.4%.
[0055] Step 2 – Elimination Reaction: Add 800g methanol and 1045g of the product from Step 1 to a 3L reactor, stir and heat to 55℃. Slowly add 600g of 15% KOH methanol solution (90g KOH, 1.61mol), controlling the temperature at 60-65℃, completing the addition over 2 hours. Maintain the temperature for 2 hours, add 500g water, and let stand for 30 minutes. Separate the layers, wash with water until neutral, and dry with anhydrous sodium sulfate. Collect the fraction at 82-84℃ / 50mm Hg by distillation to obtain perfluorohexylethylene (C6F). 13 CH=CH2) 785g, GC purity 99.2%, yield 98.0%.
[0056] Step 3 – Addition Reaction: Add 400g isopropanol and 2g BF3·Et2O to a 2L autoclave, and stir to 155℃. Slowly pump in 785g of perfluorohexylethylene solution containing 8g BF3·Et2O using a metering pump, completing the pumping process over 3 hours, controlling the temperature at 155-165℃ and the pressure at 1.5-1.8MPa. After pumping, maintain the temperature for 1 hour. Cool down and discharge the product, collecting the fraction at 118-120℃ / 10mmHg by distillation to obtain perfluorohexylisopropanol (C6F3·Et2O). 13 CH2CH2OCH(CH3)2) 812g, GC purity 99.1%, yield 95.0%.
[0057] Step 4 – Transesterification and Intelligent Separation: The catalyst used was the Nafion@PDMAEMA catalyst from Preparation Example 1 (the PDMAEMA grafting amount was determined to be 8.5 wt% by TGA).
[0058] Add 500g of perfluorohexyl isopropanol, 180g of methyl methacrylate (20% excess), 15g of Nafion@PDMAEMA catalyst (3wt%), 0.15g of MEHQ, and 0.05g of phenothiazine to a 2L reactor. Raise the temperature to 110℃, maintain the column top temperature at 65℃, and continuously collect the methanol-methyl methacrylate azeotrope. After 6 hours of reaction, raise the reactor temperature to 125℃, reduce the pressure to 50kPa, and continue the reaction for another hour. Sampling analysis showed that the propanol content of the feedstock was 0.8%, and the reaction was stopped.
[0059] Cool to 60°C, add triethylamine dropwise to adjust pH to 8.5, and stir for 30 minutes. Stop stirring; the catalyst will completely settle within 2 minutes. Transfer the supernatant to a distillation vessel, first distill off excess methyl methacrylate under normal pressure, then collect the fraction at 135-137°C / 5 mmHg under reduced pressure to obtain 532 g of perfluorohexyl isopropyl methacrylate, with a GC purity of 99.3% and a yield of 92.6%.
[0060] Total yield: 96.4% × 98.0% × 95.0% × 92.6% = 83.0%.
[0061] Example 2. Preparation of perfluoroethyl neopentyl acrylate (C2 series): Step 1 – Addition reaction: Using pentafluoroiodoethane (C2F5I) as the starting material, the procedure was the same as in Example 1. Perfluoroethyl ethyl iodide was obtained in 98.2% yield.
[0062] Step 2 – Elimination reaction: The procedure is the same as in Example 1. Perfluoroethyl ethylene is obtained in 92.5% yield.
[0063] Step 3 – Addition reaction: Using neopentyl alcohol as the starting material, the procedure was the same as in Example 1 (temperature adjusted to 160°C). Perfluoroethyl neopentyl alcohol was obtained in 82.4% yield.
[0064] Step 4 – Transesterification and Intelligent Separation: Using methyl acrylate as the raw material, the procedure was the same as in Example 1. Perfluoroethyl neopentyl acrylate was obtained, with a yield of 77.5%.
[0065] Total yield: 98.2% × 92.5% × 82.4% × 77.5% = 58.0%.
[0066] Mechanism analysis: The overall yield of the C2 series is significantly lower than that of the C6 series. The main reasons are as follows: (1) In the third step of the alcohol addition reaction, the boiling point of C2 perfluoroalkyl ethylene is relatively low (about 30-35℃). In the high temperature and pressure reaction, some of it is vaporized, resulting in a decrease in effective concentration, and a decrease in reaction rate and yield. (2) The C2 perfluoroalkyl chain is relatively short and has poor compatibility with alcohols, which limits the mass transfer between the two phases. (3) Neopentyl alcohol has a large steric hindrance, which reduces the nucleophilic attack rate.
[0067] Example 3. Preparation of perfluoroisopropylpropyl methacrylate (C3 isomer system): Step 1 – Addition reaction: Using heptafluoroisopropyl iodine ((CF3)2CFI) as the starting material, the procedure was the same as in Example 1. Heptafluoroisopropylethyl iodine was obtained in 98.5% yield.
[0068] Step 2 – Elimination reaction: The procedure is the same as in Example 1. Heptafluoroisopropylethylene is obtained in 94.2% yield.
[0069] Step 3 – Addition reaction: Using isopropanol as the starting material, the procedure was the same as in Example 1. Heptafluoroisopropylisopropanol was obtained in 95.5% yield.
[0070] Step 4 – Transesterification and Intelligent Separation: Using methyl methacrylate as the raw material, the procedure was the same as in Example 1. Heptafluoroisopropylisopropyl methacrylate was obtained, with a yield of 93.5%.
[0071] Total yield: 98.5% × 94.2% × 95.5% × 93.5% = 82.9%.
[0072] Mechanism analysis: The overall yield of the C3 isomer series (82.9%) was comparable to that of the C6 linear series (83.0%), indicating that branched perfluoroalkyl groups had no significant adverse effect on the reaction yield. However, the yield of the second elimination reaction (94.2%) was slightly lower than that of the C6 (98.0%). This is because the β-hydrogen of the heptafluoroisopropyl group is affected by the electron-withdrawing effect of the two CF3 groups, resulting in stronger acidity but also greater steric hindrance. E2 elimination requires a more stringent conformation, leading to a slight decrease in yield.
[0073] Example 4. Preparation of perfluorobutylpropyl methacrylate (C4 series): Step 1 – Addition reaction: Using perfluoro-n-butyl iodine (C4F9I) as the starting material, the procedure was the same as in Example 1. Perfluorobutylethyl iodine was obtained in 97.5% yield.
[0074] Step 2 – Elimination reaction: The procedure is the same as in Example 1. Perfluorobutylethylene is obtained in 96.8% yield.
[0075] Step 3 – Addition reaction: Using isopropanol as the starting material, the procedure was the same as in Example 1. Perfluorobutylisopropanol was obtained in 94.2% yield.
[0076] Step 4 – Transesterification and Intelligent Separation: Using methyl methacrylate as the raw material, the procedure was the same as in Example 1. Perfluorobutyl isopropyl methacrylate was obtained, with a yield of 91.5%.
[0077] Total yield: 97.5% × 96.8% × 94.2% × 91.5% = 81.3%.
[0078] Example Group 5. First Step Reaction Temperature Optimization Experiment: Based on the first step reaction of Example 1, with other conditions fixed, the effect of different reaction temperatures on the yield was investigated.
[0079] Table 2. Results of the first-step reaction temperature optimization experiment
[0080] As shown in Table 2, the yield significantly increased from 78.5% to 96.4% when the temperature increased from 50℃ to 70℃. Mechanism: The half-life of AIBN is closely related to temperature—at 50℃, the half-life is about 4.5 hours, the initiation rate is slow, and the free radical concentration is low; at 70℃, the half-life is about 0.5 hours, the initiation rate is suitable, and the free radical chain reaction proceeds fully.
[0081] As the temperature continues to rise to 90-100℃, the yield actually decreases. Mechanism: Excessively high temperatures lead to rapid decomposition of AIBN, resulting in excessively high free radical concentrations and exacerbating side reactions such as bimolecular termination; simultaneously, the solubility of ethylene decreases at high temperatures, reducing the effective reaction concentration; and perfluoroalkyl iodides may also undergo partial thermal decomposition. Optimal temperature range: 60–90℃.
[0082] Example Group 6. Fourth step: Catalyst dosage optimization experiment: Based on step 4 of Example 1, with other conditions fixed, the effect of the amount of Nafion@PDMAEMA catalyst on the yield and separation effect was investigated.
[0083] Table 3. Results of the fourth step catalyst dosage optimization experiment.
[0084] Table 3 shows that increasing the catalyst dosage from 1% to 3% significantly accelerated the reaction rate (12h → 6h) and improved the yield (85.3% → 92.6%). Mechanism: The catalyst provides acidic active sites for the transesterification reaction; increasing the dosage increases the number of active sites and thus the reaction rate.
[0085] Increasing the catalyst dosage from 3% to 7% did not significantly change the yield (92.6%→93.1%→92.8%), but prolonged the settling time (2 min→4 min). Mechanism: Excessive catalyst particle concentration increases the collision frequency between particles during pH-responsive aggregation, but the resulting aggregates are more porous, leading to a decrease in settling velocity. Furthermore, excessive catalyst dosage increases the cumulative loss of acidic sites during regeneration, reducing cycle stability. Optimal catalyst dosage: 2-3 wt%.
[0086] Comparative Example 1. Comparison of unmodified Nafion catalyst types: Based on step four of Example 1, three catalyst systems were compared.
[0087]
[0088] Table 4. Catalytic effect of unmodified Nafion catalyst As shown in Table 4, the catalytic activity of the three products was not significantly different (92.3% to 94.1%), indicating that the PDMAEMA modification did not significantly affect the acidic catalytic activity of Nafion. This suggests that the PDMAEMA was only modified on the surface of the support and did not enter the hydrophilic channels enriched with sulfonic acid groups in Nafion, with a sulfonic acid group retention rate of >90%.
[0089] Separation results: Nafion@PDMAEMA sedimentation took only 2 minutes, while unmodified Nafion required 45 minutes of pressure filtration. This indicates that the surface of unmodified Nafion particles lacks pH responsiveness and remains suspended in the reaction solution due to electrostatic repulsion, requiring external force for separation. At pH 8.5, the PDMAEMA on the Nafion@PDMAEMA surface deprotonates and hydrophobically shrinks, generating hydrophobic attraction between particles, leading to spontaneous aggregation and sedimentation.
[0090] Cyclic stability: After 10 cycles of Nafion@PDMAEMA, the activity decreased by only 3%, which was better than that of unmodified Nafion (decreased by 5.5%). This indicates that the mechanical abrasion of unmodified Nafion during filtration and recovery leads to particle breakage and loss; pH-responsive sedimentation is a mild physical aggregation process that does not cause mechanical damage to the particles.
[0091] Comparative Example Group 2. Comparative Test of Polymerization Inhibitor Systems: Based on step four of Example 1, the effects of different polymerization inhibitor systems on the polymerization inhibition effect of the product were compared.
[0092] Table 5. Differences between single-component polymerization inhibitors and composite polymerization inhibitor systems
[0093] Table 5 shows that the total polymerization loss is as high as 13.7% without a polymerization inhibitor, and the product is severely discolored. Mechanism: The double bonds of methacrylate are prone to thermally initiated free radical polymerization at high temperatures (>100℃), resulting in polymer formation that leads to decreased yield and product discoloration.
[0094] When used alone, MEHQ showed a reasonable inhibitory effect in the reaction stage (0.8%), but the polymerization rate in the distillation stage still reached 2.3%. Mechanism: MEHQ is a phenolic polymerization inhibitor that terminates free radicals through chain transfer mechanism, but its antioxidant capacity decreases at high temperatures (distillation temperature > 130℃), resulting in reduced polymerization inhibition efficiency.
[0095] Phenothiazine is more effective than MEHQ when used alone. Mechanism: Phenothiazine is a free radical scavenger and has better stability than phenols at high temperatures.
[0096] The combination of MEHQ and phenothiazine yields the best results (total polymerization loss of only 0.7%). Mechanism: The two work synergistically—MEHQ captures free radicals in the liquid phase, while phenothiazine supplements this capture at the gas-liquid interface and in the high-temperature region, forming a full-space free radical protection network. The superposition of their different mechanisms of action produces a synergistic effect of "1+1>2".
[0097] Comparative Example Group 3. Separation Method Comparison Experiment: Using the liquid material after the fourth step of the reaction in Example 1 as the subject, three solid-liquid separation methods were compared.
[0098] Table 6. Comparison of Separation Methods and Results
[0099] Table 6 shows that: natural sedimentation (unmodified catalyst): only 45.3% of the catalyst was recovered after 120 minutes. Mechanism: Nafion particles with a diameter of 0.5-1.0 mm are stably suspended in the reaction solution due to electrostatic repulsion, while Stokes particles settle at an extremely slow rate.
[0100] pH-responsive sedimentation: 99.5% recovery in 2 minutes. Mechanism: After deprotonation, PDMAEMA hydrophobically aggregates, increasing the effective particle size from millimeters to centimeter-sized aggregates, and increasing the sedimentation rate by 3-4 orders of magnitude.
[0101] Centrifugal separation: recovery rate 98.2%, but energy consumption is 7.5 times that of pH-responsive sedimentation. Mechanism: Centrifugation relies on mechanical force for forced separation, and energy consumption is proportional to the square of the rotational speed.
[0102] Precision filtration: Lowest recovery rate (96.5%), longest time (45 minutes). Mechanism: Nafion particles have a certain degree of elasticity and stickiness, which easily clogs the filter cartridge pores, requiring frequent backflushing or filter cartridge replacement.
[0103] Economic analysis: Based on an annual production of 1,000 tons of products, pH-responsive sedimentation saves approximately 130,000 yuan in electricity costs compared to centrifugal separation, and approximately 200,000 yuan in filter replacement costs compared to precision filtration.
[0104] Comparative Example Group 4. Catalytic System Comparison Experiment: Based on step four of Example 1, the overall environmental protection indicators of different catalytic systems were compared.
[0105] Table 7. Comparison of catalytic effects between homogeneous acids and solid acids
[0106] Table 7 shows the wastewater generation: Homogeneous acid requires water washing and neutralization, generating 0.85-1.20 tons of fluoride- and acid-containing wastewater per ton of product. This invention uses solid acid + pH response separation, eliminating the need for water washing, and generates only 0.05 tons of wastewater per ton of product (from equipment cleaning), achieving a reduction rate >90%.
[0107] Equipment corrosion: Concentrated sulfuric acid corrodes stainless steel at a rate of 0.35 mm / a, requiring the use of glass-lined or Hastelloy-lined equipment. Nafion resin, a solid organic acid, corrodes equipment at a rate of only 0.02 mm / a and is compatible with conventional stainless steel.
[0108] Catalyst recovery: Homogeneous acid is completely consumed and cannot be recovered; solid acid recovery rate >95%.
[0109] Comparative Example Group 5. Application Performance Comparison Test: The application performance of perfluorohexyl isopropyl methacrylate (C6-PFMA) prepared in Example 1 was compared with that of commercially available perfluorooctyl ethyl methacrylate (C8-PFMA, containing PFOA impurities).
[0110] Test method: Prepare a 1% mass fraction of ethyl acetate solution for the monomer; immerse the polyester fabric for 10 minutes, with a roll-off rate of 70%, dry at 120℃ for 3 minutes, and bake at 160℃ for 2 minutes; test the water contact angle according to AATCC 22 standard and the oil repellency rating according to AATCC 118 standard.
[0111] Table 8. Performance comparison between the C6 product of Example 1 and the commercially available C8 product
[0112] As shown in Table 8, the performance of the C6 product of this invention exceeds that of commercially available C8 products: water contact angle 116° > 114 to 115°, surface energy 12.5 < 12.8 to 13.2 mN / m. Mechanism: This invention, through the design of an isopropyl branched structure, enables the perfluorohexyl chains to form a more ordered arrangement on the surface. The steric hindrance effect of the isopropyl group forces the perfluoroalkyl chains to extend outward at a near-vertical angle, resulting in a higher enrichment density of the CF3 end groups on the surface, thus achieving a lower surface energy. In traditional straight-chain C8 products, the perfluoroalkyl chains exhibit a certain degree of tilting and entanglement.
[0113] The C6 product of this invention exhibits superior water resistance: after 20 washes, the contact angle decreases by only 8° (116→108), compared to a 12-13° decrease in commercially available C8 products. Mechanism: The hydrophobicity of the isopropyl group enhances the compatibility and anchoring force between the monomer and the polymer matrix, reducing the migration and loss of fluorinated segments during use.
[0114] Conventional C6 products exhibit significantly poor performance: a water contact angle of only 102°. Mechanism: Short-chain products without molecular structure optimization cannot form dense, ordered surface assemblies due to the perfluoroalkyl chains, resulting in higher surface energy.
[0115] Environmental compliance: The PFOA content of the product of this invention is <1ppb, which is far below the limit of the EU REACH regulation (25ppb); commercially available C8 products contain 850-1250ppb of PFOA impurities, which are restricted substances.
[0116] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A preparation process for a series of functional chemicals containing perfluoroalkyl groups, characterized in that, Includes the following steps: S1. Using perfluoroalkyl halides with 1-6 carbon atoms as raw materials, in the presence of a free radical initiator, an addition reaction is carried out with ethylene at 30-200°C and 0-1.5 MPa pressure to generate perfluoroalkyl ethyl halides; S2. The product of S1 is subjected to an elimination reaction in an alkali metal hydroxide alcohol solution at 25–80 °C to generate perfluoroalkyl ethylene; S3. The product of S2 is reacted with a monohydric alcohol in the presence of a Lewis acid catalyst at 120–180 °C and 1.2–2.5 MPa pressure to produce perfluoroalkyl propanol; S4. The product of S3 is subjected to transesterification reaction with acrylate or methacrylate in the presence of a solid acid catalyst with a pH-responsive polymer modified on its surface and a composite polymerization inhibitor at 70–150 °C. After the reaction is completed, an alkali is added to the system to adjust the pH to weakly alkaline, causing the pH-responsive polymer to deprotonate and drive the catalyst particles to aggregate and settle. The catalyst is recovered, and the filtrate is distilled to obtain the target product.
2. The preparation process according to claim 1, characterized in that, The perfluoroalkyl group of the perfluoroalkyl halide includes, but is not limited to, perfluoromethyl, perfluoroethyl, perfluoron-propyl, perfluoroisopropyl, perfluoron-butyl, perfluoroisobutyl, perfluoron-hexyl, and perfluoroisohexyl, and the halogen group is iodine or bromine.
3. The preparation process according to claim 1, characterized in that, The free radical initiator in S1 is azobisisobutyronitrile, and the amount used is 0.1% to 2.0% of the mass of the perfluoroalkyl halide; the reaction temperature is 60 to 90°C, and the pressure is 0.35 to 0.70 MPa.
4. The preparation process according to claim 1, characterized in that, The alkali metal hydroxide alcohol solution in S2 is an ethanol solution of potassium hydroxide or a methanol solution of potassium hydroxide, with an alkali concentration of 5% to 30% and a molar ratio of alkali to raw material of 1.0 to 1.5:1; the reaction temperature is 50 to 70°C.
5. The preparation process according to claim 1, characterized in that, In step S3, the Lewis acid catalyst is a boron trifluoride diethyl ether complex or a supported BF3 catalyst, and the amount used is 0.5% to 5.0% of the mass of perfluoroalkyl ethylene; the supported BF3 catalyst is BF3 / MCM-41 or BF3 / SiO2, and the catalyst is recovered by filtration after the reaction; the monohydric alcohol is any one of methanol, ethanol, propanol, isopropanol, tert-butanol or neopentyl alcohol; the reaction temperature is 150 to 165°C.
6. The preparation process according to claim 1, characterized in that, The pH-responsive polymer in S4 is covalently grafted onto the surface of a solid acid carrier via surface-initiated atom transfer radical polymerization or chemical bonding; the pH-responsive polymer is any one of poly(2-dimethylamino)ethyl methacrylate, poly(4-vinylpyridine), or polymethacrylic acid.
7. The preparation process according to claim 1, characterized in that, The solid acid catalyst support in S4 is any one of Nafion perfluorosulfonic acid resin, sulfuric acid-promoted zirconium oxide, or sulfonated polystyrene-divinylbenzene resin.
8. The preparation process according to claim 1, characterized in that, The catalyst used in S4 is 1% to 5% of the mass of perfluoroalkyl propanol; the recovered catalyst is regenerated by washing with dilute acid to pH 3.0 to 4.0, and the catalytic activity decreases by less than 5% after being recycled more than 10 times.
9. The preparation process according to claim 1, characterized in that, After the reaction in S4 is completed, the pH needs to be adjusted to a weakly alkaline range of 7.5 to 9.0, and the base used is any one of triethylamine, triethanolamine, or ammonia.
10. The preparation process according to claim 1, characterized in that, In step S4, the composite polymerization inhibitor system consists of a phenolic polymerization inhibitor and a free radical scavenger. The phenolic polymerization inhibitor is p-hydroxyanisole, and the free radical scavenger is phenothiazine. The mass ratio of the two is 2:1 to 5:1, and the total amount used is 200 to 500 ppm of the total mass of the reaction solution.